Literature ratified knowledge based view of poultry supply chain integration concept - Ariffin, Ahmad Shabudin; Abas, Zakaria; Baluch, Nazim Hussain (Penerbit UTM Press, 2015)
The evolution of relationships based on collaboration between business partners has become a fundamental subject of research in the area of supply chain management; including poultry supply chain integration.Study in this field has focused on a range of integration models.This study focuses on integration of systems, processes and strategy which is important for poultry supply chain business partners to recognize the benefits of closely associating supply to demand.One need to realize that these benefits are not easily achieved without constraints.A conclusion was made by proposing that ‘Knowledge Based View’ is a resource that can contribute value, towards knowledge generation, acquisition and application among members within and between organizations.